Sarcomatoid (Spindle Cell) Carcinoma of Tongue: A Report of Two Cases - Montserrat Reyes; Gina Pennacchiotti; Fabio Valdes; Rodrigo Montes; Marcelo Veloso; Maria Angélica Matamala; Luis Zanolli; Gonzalo Rojas-Alcayaga (Case Reports in Dentistry)
Sarcomatoid Carcinoma (SC) is an unusual and aggressive variant of squamous cell carcinoma, which frequently recurs and metastasizes; for this reason, the right diagnosis is very important. It is considered to be a biphasic tumor made up of cells from squamous and spindle cells carcinoma with a sarcomatous aspect, but of epithelial origin. The diagnosis often represents a clinical-pathological challenge where the study with immunohistochemical technique (IHC) is key to the histopathological diagnosis. The reported cases related to oral mucosa are limited. In this work we present two SC cases where the use of IHC allowed us to achieve a conclusive diagnosis.